2018
DOI: 10.1016/j.celrep.2018.10.028
|View full text |Cite
|
Sign up to set email alerts
|

SNIP1 Recruits TET2 to Regulate c-MYC Target Genes and Cellular DNA Damage Response

Abstract: SUMMARY The TET2 DNA dioxygenase regulates gene expression by catalyzing demethylation of 5-methylcytosine, thus epigenetically modulating the genome. TET2 does not contain a sequence-specific DNA-binding domain, and how it is recruited to specific genomic sites is not fully understood. Here we carried out a mammalian two-hybrid screen and identified multiple transcriptional regulators potentially interacting with TET2. The SMAD nuclear interacting protein 1 (SNIP1) physically interacts with TET2 and bridges T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 56 publications
5
61
0
Order By: Relevance
“…It was found that TET2 interacts with IDAX protein whose CXXC domain binds to unmethylated CpG dinucleotides in the promoter but in a sequence-nonspecific manner [31]. A very recent report described the mechanism for targeting TET2 to specific promoters [36]. It was proposed that transcriptional co-activator SMAD nuclear interacting protein 1 (SNIP1) bridges TET2 to bind to a sequencespecific DNA-binding factor c-MYC, thus facilitating the recruitment of TET2 to regulate c-MYC target genes by promoting DNA demethylation at the promoters [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that TET2 interacts with IDAX protein whose CXXC domain binds to unmethylated CpG dinucleotides in the promoter but in a sequence-nonspecific manner [31]. A very recent report described the mechanism for targeting TET2 to specific promoters [36]. It was proposed that transcriptional co-activator SMAD nuclear interacting protein 1 (SNIP1) bridges TET2 to bind to a sequencespecific DNA-binding factor c-MYC, thus facilitating the recruitment of TET2 to regulate c-MYC target genes by promoting DNA demethylation at the promoters [36].…”
Section: Discussionmentioning
confidence: 99%
“…A very recent report described the mechanism for targeting TET2 to specific promoters [36]. It was proposed that transcriptional co-activator SMAD nuclear interacting protein 1 (SNIP1) bridges TET2 to bind to a sequencespecific DNA-binding factor c-MYC, thus facilitating the recruitment of TET2 to regulate c-MYC target genes by promoting DNA demethylation at the promoters [36]. In addition, it is well established that the posttranslational modification, monoubiquitylation, which is catalyzed by CRL4VprBP E3 ligase, promotes the DNA binding of TET2 by stabilizing the conformation of TET2 complexed with DNA (where the monoubiquitylation site directly contacts the DNA) [32,37].…”
Section: Discussionmentioning
confidence: 99%
“…Within Cluster 12, MYC was by far the most abundantly expressed TF in hematopoietic stem cells. It has previously been reported that DNA methylation inhibits MYCN chromatin binding in Tet1-3 triple knockout ES cells (Yin et al 2017), and a recent study has uncovered that TET2 is recruited to MYC binding sites by SNIP1 in cancer cell lines (Chen et al 2018). However, analysis of chromatin accessibility by diffTF at MYC binding sites (predicted individually from all available MYC DNA-binding motifs) did not show a significant difference in wild-type and Tet2 knockout, possibly due to a complex MYC binding pattern at E-boxes throughout the genome.…”
Section: Basic Helix-loop-helix (Bhlh) Tfs Are Adversely Affected By mentioning
confidence: 98%
“…Smad nuclear interacting protein 1 (SNIP1), as an evolutionarily conserved nuclear protein, is involved in essential biological processes such as cell proliferation ( Roche et al, 2004 ; Fujii et al, 2006 ), small RNA biogenesis ( Yu et al, 2008 ), DNA damage response ( Chen et al, 2018 ), and several signaling pathways ( Kim et al, 2000 ; Kim et al, 2001 ). In patients with non-small cell lung cancer or tongue squamous cell carcinoma, SNIP1 might be a reliable prognostic indicator ( Liang et al, 2011 ; Jeon et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%